2015
DOI: 10.1115/1.4030852
|View full text |Cite
|
Sign up to set email alerts
|

Wingtip Vortex Control Via Tip-Mounted Half-Delta Wings of Different Geometric Configurations

Abstract: The control of the tip vortex, generated by a rectangular NACA 0012 wing, via tip-mounted half-delta wings (HDWs), of different slendernesses Λ, root chords cr, and deflections δ, was investigated experimentally at Re = 2.45 × 105. The results show that regardless of Λ, cr, and δ, the addition of HDWs consistently led to a diffused tip vortex. The degree of diffusion was, however, found to increase with decreasing Λ and cr. HDWs with cr ≤ 50% of the baseline-wing chord c caused a rapid diffusion of vorticity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…9 More recent studies consider both passive and active measures to reduce the strength and persistence of tip vortices. Passive techniques are considered by Lee and Su, 10 Lee and Choi, 11 who show experimentally that a reverse half-delta wing mounted to the tip of a NACA0012 foil resulted in a weaker tip vortex being produced. Active techniques such as the use of flaps have also been considered.…”
Section: Introductionmentioning
confidence: 99%
“…9 More recent studies consider both passive and active measures to reduce the strength and persistence of tip vortices. Passive techniques are considered by Lee and Su, 10 Lee and Choi, 11 who show experimentally that a reverse half-delta wing mounted to the tip of a NACA0012 foil resulted in a weaker tip vortex being produced. Active techniques such as the use of flaps have also been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the RDW vortex of the slender wing became singular and attained axisymmetry at x /c = 1.5 (see Figure 8(h)), which is similar to the wingtip vortex developed in the near field behind an NACA 0012 wing. 12 The variation of the critical RDW50 vortex flow parameters with x /c at α = 10° is summarized in Figure 9(a) to (e) (denoted by the ◊ symbols).
Figure 8.Representative iso-ζc/u ∞ contours of the RDW vortex at selected x /c for α = 10°.
…”
Section: Resultsmentioning
confidence: 99%
“…The RDWs has also been employed in the control of the wingtip vortex generated by a rectangular NACA 0012 wing at Re = 3.45 × 10 5 by Lee and Choi. 12 Lee and Choi found that, regardless of its root chord and sweep angle, the tip-mounted reverse half-delta wings always caused a rapid diffusion and breakdown of the wingtip vortex. The vortex produced by the small-chord half-delta wing interacted with the vortex from the regular NACA 0012 wing, causing both vortices to break down, which gave the benefit of reduced lift-induced drag.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, the span-dominated ground effect on the wingtip vortices and the lift-induced drag generated by a (2012)). More recently, an alternative wingtip vortex control was proposed by Lee and Choi (2015) by using a tip-mounted small-chord half-delta wings (HDW) of different slenderness Λ, root chords c r , and deflections. Lee and Choi (2015) reported that, regardless of Λ and c r , the addition of a small HDW to the tip of a rectangular semi-wing at Re = 2.45 × 10 5 triggered the breakdown of the tip vortex, producing a greatly diffused and circulation flow-like tip vortex (Figure 5B) as compared to its baseline-wing Frontiers in Aerospace Engineering frontiersin.org counterpart (Figure 5A).…”
Section: Ogementioning
confidence: 99%
“…More recently, an alternative wingtip vortex control was proposed by Lee and Choi (2015) by using a tip-mounted small-chord half-delta wings (HDW) of different slenderness Λ, root chords c r , and deflections. Lee and Choi (2015) reported that, regardless of Λ and c r , the addition of a small HDW to the tip of a rectangular semi-wing at Re = 2.45 × 10 5 triggered the breakdown of the tip vortex, producing a greatly diffused and circulation flow-like tip vortex (Figure 5B) as compared to its baseline-wing Frontiers in Aerospace Engineering frontiersin.org counterpart (Figure 5A). The streamwise vorticity ζ = zw/zy − zv/zz was calculated from the vw-crossflow measurements by using a central differencing scheme to evaluate the derivatives.…”
Section: Ogementioning
confidence: 99%